Analysis of the Development of the Unemployment Rate in Lithuania: Application of the SVAR Model - Reichenbachas, Tomas (Ekonomika, 2015)
The paper analyses the dynamics of unemployment in Lithuania, using a structural vector autoregressive model (sVAR) with long-term restrictions proposed by Fabiani et al. (2001). In accordance with it, the unemployment rate is predetermined by economic shocks, some of them with long-term effects (structural) and some with short-term ones (cyclical). The greater part of changes in unemployment in the period of 2002 to 2014 were predetermined by cyclical shocks (of productivity and labour supply and demand). The cyclical unemployment, peaked in the years 2010 to 2011, amounted to ca. 6%. On the other hand, structural unemployment is slow to change, in the years of the economic boom (2006 to 2007) it amounted to ca. 8% (at the time, the cyclical unemployment was negative and the economy encountered overheating, while in 2014 structural unemployment was slightly higher and amounted to ca. 11%).
Keywords: unemployment; hysteresis; SVAR